TRADISI DAN PENDIDIKAN KALIGRAFI AL-QUR'AN SEBAGAI PRESERVASI SENI ISLAM: ANALISIS RESILIENSI DI PONDOK PESANTREN KALIGRAFI SAKAL JOMBANG - Nurhadi Muhammad Mukhlis; M. Amiq Fahmi; Abdul Najib (Jurnal Studi Pesantren, 2026)
This study aims to analyse how the tradition and education of Al-Qur'an calligraphy at the SAKAL Jombang Calligraphy Islamic Boarding School functions as a form of cultural resilience in the preservation of Islamic art amid modernity. The scope of this research focuses on the pesantren's adaptation strategies using Michael Ungar's social-ecological resilience theory framework. The research method used is descriptive qualitative with a field research approach. Data was collected through observation, in-depth interviews with caregivers, students, and alumni, as well as documentation studies. The results of the study show that SAKAL develops cultural resilience through four of Ungar's principles: (1) Decentralisation, with the sanad system and the pesantren environment as the backbone of scientific transmission; (2) Complexity, through dynamic navigation between involvement in modern competition while maintaining a traditional scientific orientation; (3) Atypicality, with strategies such as restricting instant digital learning and adhering to classical texts, which are effective in maintaining authenticity; and (4) Cultural Relativity, where standards of success are measured through the regeneration of sanad, not individual achievements